Life after party ; the high cost of dying ; Horror SFX - Gancia, Carol; Lazaro, Cheche; Nakpil, Henry; Ong, James Jonathan (Quezon City Probe Productions, 1995)
Presents viewpoints of Christians, Hindus, Ignostics, skeptics, after-life believers on life after death ; funeral parlor servicing bereaved families of all social classes ; and the use of computer softwares and high tech mainframes in creating unearthly things like ghost and in transforming a normal person to monster.
Life after party (12 min.) -- The high cost of dying (13 min.) -- Horror SFX (12 min.)
VHS.
Credits : Reporter, Luchi Cruz-Valdes.
Keywords: Capitol Funeral Homes (Quezon City, Philippines); Immortality (Philosophy).; Computer software; Funeral services -- Philippines; Reincarnation